23.2: Invited Paper: Influence of the Ambient Illuminance on the Subjective Brightness Measurements. (28th November 2018) - Yang, Lanlan; Li, Shuai; Tu, Yan; Zhang, Yuning; Wang, Lili; Li, Xiaohua
Abstract : The subjective brightness is determined by not only the display screen luminance but also the light surrounding the display. A metric for space brightness named "Feu" is adopted to consider the effect of luminance distribution. The relation between the pupil diameter and the space brightness is applied to obtain the subjective brightness. The measured subjective brightness is obtained both for direct‐view display and AR display. The results indicate that the measured subjective brightness is much closer to the perceived result. The subjective brightness increases along with the increase of the screen luminance at the same ambient illuminance. While at the same screen luminance, the subjective brightness decreases with the increase of the ambient illuminance in most cases.